ASSESSMENT OF ANTERIOR CHAMBER ANGLE ON ANTERIOR SEGMENT OPTICAL COHERENCE TOMOGRAPHY IN PATIENTS WITH ANGLE CLOSURE GLAUCOMA AND ANGLE CLOSURE SUSPECTS - Bhutto, SA; LEGHARI , AA; KATPAR, NA; GOPANG, Z; SHAIKH, DYD; GUL, PA (Biological and Clinical Sciences Research Journal, 2024)
The objective of this cross-sectional study was to determine the anterior chamber angle using anterior segment optical coherence tomography (AS-OCT) in patients diagnosed with angle closure glaucoma and angle closure suspects. The research was conducted at Shaheed Mohtarma Benazir Bhutto Medical University Larkana, spanning from March 3, 2022, to June 30, 2023. Patients meeting the inclusion criteria and diagnosed with primary angle-closure glaucoma (PACG) were enrolled in the study after obtaining informed consent. The procedure, risks, and benefits of the study were explained to the patients before obtaining consent. AS-OCT was utilized to evaluate patients suspected of primary angle closure and those with confirmed primary angle closure. The results revealed a mean age of 56.21 ± 12.31 years among the study participants, with a confidence interval of 55.04 to 57.38. The mean duration of primary angle closure glaucoma was 22.52 ± 10.98 months, with a confidence interval of 21.47 to 23.57. Of the 423 patients included in the study, 219 (52%) were male, and 204 (48%) were female. Primary angle closure suspect and primary angle closure were observed in 47 (11%) and 44 (10%) patients, respectively. In conclusion, older age, higher central corneal thickness (CCT), and shorter axial length or presence of hyperopia were identified as important independent predictors of suspicion of primary angle closure and primary angle closure. These findings underscore the significance of thorough assessment and monitoring of these parameters in patients at risk of angle closure glaucoma.